Effects of Public Premiums on Children's Health Insurance Coverage: Evidence from 1999 to 2003 - Genevieve Kenney; Jack Hadley; Fredric Blavin (SAGE Publishing, 2006)
This study uses 2000 to 2004 Current Population Survey data to examine the effects of public premiums on the insurance coverage of children whose family incomes are between 100% and 300% of the federal poverty level. The analysis employs multinomial logistic models that control for factors other than premium costs. While the magnitude of the estimated effects varies across models, the results consistently indicate that raising public premiums reduces enrollment in public programs, with some children who forgo public coverage having private coverage instead and others being uninsured. The results indicate that public premiums have larger effects when applied to lower-income families.